Model of Post-Pandemic Human Resource Strategy in Indonesian Private Companies - Dipa Teruna; Tedy Ardiansyah (Majalah Ilmiah Bijak, 2023)
Human resources are a problem that is often faced by every company, especially when coupled with the COVID-19 pandemic. Companies must continue to survive by getting benefits with the right human resource strategy, but the paradoxical reality is that hundreds of companies have closed their businesses due to increasingly serious problems. be it internal or external. The purpose of this research is to find out how big the relationship is between each informant and what indicators influence each of these variables. This research was carried out with a phenomenological qualitative approach, in which phenomenologists describe the essence of the big things from each person's part of their life experience. Phenomenologists must describe in detail where they obtain or experience a phenomenon from each individual. Five informants with decades or decades of experience and the highest positions in a company were given samples. The method used in data processing uses Nvivo12 tools. The research instrument adopts findings from previous research and theoretical studies in order to make it easier to help with problems in the human resource strategy. The results obtained showed that 4 informants had strong and moderate correlation values for each informant, and only 1 informant did not have a strong relationship. The map analysis test includes indicators that have more than one similarity from each piece of information, as well as a descriptive test that strengthens the relationship to these variables.